ANALISIS FAKTOR PENDORONG DAN PENARIK MOTIVASI WISATAWAN BERKUNJUNG KE BALI UTARA - Abdillah, Darius man (Jurnal Kepariwisataan Indonesia : Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
North Bali region has a diverse tourism potential and already known in and outside the country but the number of tourist visits are still far behind from southern Bali. This happens can not be separated from the motivation of visiting tourists. How to increase the motivation of tourists to come to visit is a problem that will be raised with the aim to show the strategy formulation to increase the motivation of tourists visiting the tourist destinations in North Bali, with attention to the factors of attraction and pusher. Analysis method using SWOT analysis. Improving the governance of tourist attraction, amenitas, accessibility, preserving nature and culture, promoting to the country of origin of tourists, and making legal signs as a poduk of local and central government policies that support the development of environmentally sound tourism are strategic steps must be done by involving various stakeholders.